A qualitative investigation of male partners' experience of relationships with women suffering from vaginismus - Sampson, Christopher (My University, 2008)
There is extensive debate on how the condition of vaginismus is understood, classified and diagnosed. A significant amount of literature argues that no school of thought has adequately explained the condition, and no terminology sufficiently describes the experience of sufferers and their partners. This study explores the experiences and perceptions of male partners to contribute towards a more meaningful understanding of the condition. The participants were volunteers who, together with their partners had sought treatment at a sexual and reproductive health clinic. Each participant consented to a semi-structured interview which explored themes around their relationship and sexual interaction, and understanding of and response to vaginismus. The interview data was analysed using content analysis and themes were drawn from the patterns identified. These themes provide a rich description of the experience of men in relationships with women diagnosed with vaginismus. There is also some support for the literature findings on the characteristics of the male partners. The participants appear to have particular personality characteristics, which are sustained in the context created by the sexual and relationship difficulties associated with vaginismus. It is aspects of the participants’ personalities and their social and cultural identities which mediate their experience in the context of the relationship. In addition, the participants’ understanding of sexual identity is strongly influenced by culturally defined norms. Although the problem may be conceptualised as a sexual difficulty, it can become pervasive and affect other aspects of the relationship. However, the condition also has the potential to amplify the importance of the relationship and lead to increased commitment. The time periods before seeking treatment varied considerably, though all the participants reported finding ways in which to manage the sexual difficulties. The couples’ main objective for seeking treatment was to have penetrative intercourse and/or conceive children. The experience of seeking treatment was hampered by inconsistent diagnoses and a lack of specialized knowledge. It is recommended that future research focuses on improving assessment and diagnosis of vaginismus
Keywords: Male partners; Relationships with women; Vaginismus